Solar driven CO2 reduction with a molecularly engineered periodic mesoporous organosilica containing cobalt phthalocyanine. Issue 5 (18th January 2023) - Angeles Navarro, M.; Sain, Sunanda; Wünschek, Maximilian; Pichler, Christian M.; Romero-Salguero, Francisco J.; Esquivel, Dolores; Roy, Souvik
Abstract : Efficient CO2 photoreduction to CO with >70% product selectivity over a periodic mesoporous organosilica-based heterogeneous catalyst containing molecular cobalt phthalocyanine units. Abstract : A molecular cobalt phthalocyanine (CoPc) catalyst has been integrated in an ethylene-bridged periodic mesoporous organosilica (PMO) to fabricate a hybrid material, CoPc-PMO, that catalyses CO2 reduction to CO in a photocatalytic system using [Ru(bpy)3 ] 2+ (bpy = 2, 2′-bipyridine) as a photosensitizer and 1, 3-dimethyl-2-phenyl-2, 3-dihydro-1 H -benzo[ d ]imidazole (BIH) as an electron donor. CoPc-PMO displays a Co-based turnover number (TONCO ) of >6000 for CO evolution with >70% CO-selectivity after 4 h irradiation with UV-filtered simulated solar light, and a quantum yield of 1.95% at 467 nm towards CO. This system demonstrates a benchmark TONCO for immobilised CoPc-based catalysts towards visible light-driven CO2 reduction.